ANTI-COVID HADITH: MAQĀṢIDĪ ANALYSIS ON THE PROPHET’S GUARANTEE ON MEDINA’S STERILITY FROM ṬĀ‘ŪN - Akbar Akbar; Arifuddin Ahmad; Zulfahmi Alwi; Darsul S. Puyu (Jurnal Adabiyah, 2021)
The insignificance of modern reality to the Prophet Muhammad [pbuh]’s statements and policies determines hadith misperception. This research examines the Prophet Muhammad [pbuh]’s assurance that Madinah was sterile from the ṭā‘ūn as a pandemic, even though Madinah was also infected with Covid-19. This study used a qualitative design utilizing library data based on al-Kutub al-Tis‘ah.  The takhrij al-ḥadīṡ technique was used to track down the data that analyzed using an integrative technique developed by Ma‘ānī al-Ḥadīṡ and Maqāṣid al-Syarī‘ah. The findings revealed that the Prophet’s declaration about Madinah’s sterility due to the disease was part of his strategy for preserving the socio-political stability of Muslims who were pioneering a new civilization. Ḥifẓ al-daulah is a notion in Maqāṣid al-Syarī‘ah, it must be taken into consideration when attempting to determine the maqāṣid of each message and the Prophet. It can dispel the perception that the Prophet Muhammad’s hadith is irrelevant to the reality of modern life. ملخص